Integrated application of inorganic and bio-fertilizers affects nitrogen losses and yield of wheat (Triticum aestivum L.) - Sibananda Darjee; Pooja LR; Ashish Khandelwal; Shiva Dhar; Manoj Shrivastava; Renu Singh (Annals of Agricultural Research, 2022)
Nitrogen (N) is one of the most indispensable nutrients needed for wheat growth and production. Indiscriminate use of inorganic fertilizers leads to N losses from the agro-ecosystem which lower soil fertility, crop yield and impair the environment. N losses in agro-ecosystem majorly occur through ammonia volatilization and denitrification. Integrated application of inorganic and bio-fertilizer could reduce the N losses by synchronizing nutrient supply and demand of crop. Therefore, a field experiment was conducted at ICAR-Indian Agricultural Research Institute, New Delhi during rabi season of 2018–19 for determining the effect of inorganic and bio-fertilizer on N losses and yield of wheat. The experiment was laid out in randomized block design (RBD) replicated thrice. The experiment comprising of eight treatments involving, control (unfertilized, Tc), Azotobacter (Ta), Mycorrhiza (Tm), Azotobacter + Mycorrhiza (Tam), NPK recommended (Tr), Tr + Azotobacter (Tra), Tr + Mycorrhiza (Trm), Tr + Azotobacter + Mycorrhiza (Tram). Results have revealed that Tram showed the highest soil available P, and K. Application of Tram recorded the higher yield (6.4 t ha-1) compared to Tr where it was obtained up to 5.8 t ha-1. The ammonia volatilization and denitrification losses were reduced by 33.7% and 34.2% respectively, with application of Tram as compared to Tr. Hence, integrated application of inorganic and bio-fertilizers could be recommended in farmers field for reducing N losses as well as increasing wheat productivity.